Essays on Access to Electricity in Sub-Saharan Africa - (:unkn) unknown (My University, 2022)
There is widespread recognition that access to affordable and reliable sources of electricity is a key determinant of economic development. Electricity is, for example, essential to development of human capital, industrial activities, and the adoption of disruptive technologies in key sectors of the economy. Nevertheless, over 820 million people, worldwide, still live without electricity. More than 80% of these people are located in Sub-Saharan Africa (SSA), particularly in rural areas. Energy poverty has detrimental economic and welfare effects. It constitutes a major impediment to economic growth and poverty reduction. The dissertation studies the drivers of modern energy services adoption in developing countries and is organized into four chapters. Chapter 1 studies the regulatory framework, the tariff structure, and the subsidy schemes for mini-grids development in Tanzania. It therefore assesses the profitability of a mini-grid electrification project in Tanzania from a private investment perspective. Using an optimization technique we find that the approved standardized small power producers' tariffs and subsidy schemes in Tanzania still do not allow mini-grid for rural electrification projects to be profitable.Chapter 2 studies the effect of mobile money adoption on households' decision to buy solar panels for electricity access in Tanzania. Using household data from Tanzania, we reveal that mobile money adoption, holding all other variables constant, leads to a 19% increase in the probability of adopting solar panels. Furthermore, we find the effect of mobile money to be positive and statistically significant for only poor households. Finally, receipt of remittances, access to credit and participation in off-farm revenue generating activities are the mediating channels through which mobile money affects the probability of adopting solar panels. Chapter 3 expands on the analysis of Chapter 2 by looking at the impact of mobile money on Seneg
Keywords: African Research